Acupuncture in Pain Management: A Neurophysiological and Clinical Perspective - Mohd. Wasiullah; Piyush Yadav; Deepak Kumar Yadav; Vikash Vishawakarma (Recent Trends in Infectious Diseases, 2024)
Acupuncture, a key component of traditional Chinese medicine, has gained widespread recognition as an alternative therapy for pain management. This practice involves the insertion of fine needles into specific points on the body to influence the flow of energy or "Qi" (pronounced "chee") and restore balance. Mechanistically, acupuncture is believed to modulate pain through neurophysiological pathways, including the release of endorphins, the activation of the body's natural analgesic systems, and the regulation of inflammatory responses. It also enhances local circulation, which aids in tissue repair. Clinically, acupuncture has been shown to be effective in treating various types of pain, including musculoskeletal pain (e.g., back, neck, and knee pain), neuropathic pain (e.g., post-stroke, diabetic neuropathy), and chronic pain conditions (e.g., fibromyalgia and osteoarthritis). The clinical outcomes of acupuncture are often positive, with many patients experiencing significant pain reduction, improved mobility, and enhanced quality of life. However, the effectiveness of acupuncture remains a subject of ongoing debate, with some studies suggesting placebo effects and others supporting its efficacy through robust clinical evidence. Despite these variations, acupuncture continues to be integrated into multidisciplinary pain management programs as a complementary therapy, especially for patients with chronic pain or those seeking alternatives to pharmacological treatments.
Keywords: Acupuncture; alternative therapy; analgesic; pain management; traditional Chinese medicine